2018
DOI: 10.1590/0104-6632.20180353s20160400
|View full text |Cite
|
Sign up to set email alerts
|

SIMULTANEOUS PRODUCTION OF BIOSURFACTANTS AND LIPASES FROM Aspergillus niger AND OPTIMIZATION BY RESPONSE SURFACE METHODOLOGY AND DESIRABILITY FUNCTIONS

Abstract: Microbial conversion for the synthesis of high added-value compounds, such as biosurfactants and lipases, is one of the most promising fields within the biotechnology industry, given its current development. In this study the simultaneous production of biosurfactants and lipases by Aspergillus niger in a submerged bioprocess was analyzed. Full Factorial Design (2 3) was conducted to assess the influence of the malt extract (g•L-1 ; 25, 50, 75) and soybean oil concentrations (% v/v; 0.0, 1.25, 2.5) and agitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Biosurfactant production from fungal species have extensively been described from Aspergillus spp. [41][42][43][44] using various synthetic and biobased substrates, but herein, mutant A. niger (M2) produce significantly higher amount of biosurfactant (3.3 g/L) as compared with previous studies using native A. niger strain. The mutant (A. niger M2) exhibited high emulsification index and oil displacement as compared to native strain (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosurfactant production from fungal species have extensively been described from Aspergillus spp. [41][42][43][44] using various synthetic and biobased substrates, but herein, mutant A. niger (M2) produce significantly higher amount of biosurfactant (3.3 g/L) as compared with previous studies using native A. niger strain. The mutant (A. niger M2) exhibited high emulsification index and oil displacement as compared to native strain (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The biosurfactant production during logarithmic growth phase and stationary phase of microorganisms have already been studied from various fungal species e.g., A. ustus [42], A. niger [43,44], A. flavus [43,46], A. versicolor [47], and Piper hispidum [48], and various factors influencing the total biosurfactant yield during fermentation have broadly been studied in previous few decades [42,[49][50][51][52][53][54]. From these, several studies have reported classical methods for optimization purpose by placing one factor as constant and modifying another one.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, bacterial biosurfactants are more effective in reducing surface tension to values around 27-28 mN/m (Varjani, & Upasani, 2016;Liu, et al, 2018;Zhao, et al, 2020). However, in recent decades filamentous fungi have been explored in this sense, such as Aspergillus niger, Cunninghamella echinulata and Mucor circinelloides (Silva, et al, 2018;Sperb, et al, 2018;Marques, et al, 2019).…”
Section: Solid-state Fermentation For Biosurfactant Productionmentioning
confidence: 99%
“…This means that an increase in WSO concentration led to lower surface tension, suggesting the production of biosurfactant in the culture medium. Previously, several studies demonstrated the effectiveness of hydrophobic substrates such as vegetable and waste frying oils as inductors for microbial biosurfactant production (Montero-Rodríguez, et al, 2015;Sperb, et al, 2018;Araújo, et al, 2019).…”
Section: Full-factorial Design (Ffd)mentioning
confidence: 99%
“…To achieve this therefore, a medium formulated to maximize L-asparaginase activity while minimizing biomass concentration and total protein would be ideal. The desirability function is a mathematical protocol that recommends a set of operational conditions that meet all set goals with the best desirability (Sperb et al 2018 ). The composite desirability of a multi-response function was defined as the geometric mean of the desirability of individual responses and is given by the expression; …”
Section: Multi-objective Optimization Of Response Variablesmentioning
confidence: 99%